Digital Islamic Religious Education and Tolerance: An SLR of Online Narratives in Secondary Schools - Siti Subaidah; Faqihuddin Abdul Kodir; Saluky Saluky; Dadang Saepuloh (Ideguru: Jurnal Karya Ilmiah Guru, 2026)
Religious tolerance has become a strategic priority in education within plural societies, as schools play a crucial role in shaping civic dispositions that support peaceful coexistence. Islamic Religious Education (IRE) is widely regarded as a key instrument for fostering religious moderation (wasathiyah), tolerance, and pluralism through curriculum content, pedagogical approaches, teacher roles, and institutional culture. However, its effectiveness faces growing challenges due to the expansion of digital religious authority and online narratives that can both reinforce and polarize Islamic interpretations. This study employs a Systematic Literature Review (SLR) of Scopus-indexed journal articles published between 2016 and 2026, focusing on IRE, tolerance, moderation, pluralism, and school contexts. The findings reveal that tolerance formation is most effective when moderation values are framed contextually and multidimensionally, implemented through active dialogical pedagogy, and supported by the integration of intracurricular and extracurricular activities, teacher capacity, and school leadership. In contrast, top-down and text-based moderation approaches tend to produce superficial internalization due to weak instructional design, limited teacher readiness, and institutional orthodoxy. The review also identifies a significant gap, namely the limited research examining the interaction between students’ digital religious exposure and classroom learning. As a contribution, this article proposes Digital Religious Moderation Pedagogy (DRMP) as an integrative framework to strengthen religious tolerance in secondary education.